Biplanar quadrature coil for versatile low-field extremity MRI - Yushchenko, Maksym; Choquet, Philippe; Salameh, Najat; Sarracanie, Mathieu (Frontiers in Physics, 2023)
Biplanar magnets offer extended flexibility in MRI, particularly appealing due to unmatched accessibility to the patient. At low field strength (<0.2 T), such geometries could be particularly suitable for interventional settings or purpose-built applications such as musculoskeletal imaging. In the proposed work, we present a dual-channel, biplanar coil array for low-field MRI featuring almost fully open access when sited in a biplanar magnet. The proposed detector relies on the assembly of two orthogonal biplanar coils (single transmit channel, two receive channels in quadrature) respectively interfaced with custom inductive couplers. Simulations of the B1 field in each element were performed before the quadrature coil was built and used at 0.1 T (4.33 MHz). Once assembled, the best performance in our setup was achieved in undermatched conditions in place of conventional 50-Ω matching. Phantom images display the extended coverage of the quadrature coil, with similar SNR from each individual biplanar coil. The combined images show an expected SNR gain of √2 that confirms good decoupling between the two channels (-36 dB). To the best of our knowledge, the proposed coil represents the first implementation of a biplanar geometry at low field and the first quadrature detection for a biplanar design. The open design and overall good sensitivity of our biplanar design enabled fast and quasi-isotropic 3D imaging with (1.6 × 1.6 × 2.2) mm 3 resolution in vivo in human extremities.